'I do the peer review by myself'. (15th August 2021) - Tigchelaar, Magda
Abstract : In response to increasing interest in Vygotskian sociocultural theory in second-language learning (Lantolf and Thorne, 2006; Swain, Kinnear, and Steinman, 2015) and the call for understanding language-learning processes in relation to contexts surrounding individuals (e.g., Polio and Williams, 2009; Ferris and Hedgcock, 2014), this study adopts a sociocultural approach – more specifically, an activity theory (Leont'ev, 1981) framework – to explore an undergraduate student's approach to L2 writing in a preparatory writing course. Using a single case study design (Duff, 2014), I investigated how a student from China learned to write academic papers that met the academic norms in an English as a second language (ESL) writing class in an American university. Specifically, I analyzed how his writing activity aligned with his instructor's proposed approach to a writing task. Through the analysis of course materials, the participant's written work, observations, email communications, and interviews, I tracked how his agency (Bhowmik, 2016; Casanave, 2012; Lee, 2008; Saenkhum, 2016) as a writer developed over his first semester in the ESL program. Findings indicate that while the participant did not follow the operations assigned by the instructor, he acted strategically to accomplish selected parts of his writing assignments. His mediated actions were driven by his goals and motives that were understood from within his social and cultural environments, and interacted with each other in a dynamic and constructive manner. Overall, the study underscores the need for flexible approaches to writing instruction and the usefulness of employing activity theory as a framework in studying L2 writing processes.